Advanced meteor radar installed at Tirupati: System details and comparison with different radars. Issue 21 (6th November 2014) - Rao, S. Vijaya Bhaskara; Eswaraiah, S.; Venkat Ratnam, M.; Kosalendra, E.; Kishore Kumar, K.; Sathish Kumar, S.; Patil, P. T.; Gurubaran, S.
Abstract: An advanced meteor radar, viz, Sri Venkateswara University (SVU) meteor radar (SVU MR) operating at 35.25 MHz, was installed at Sri Venkateswara University (SVU), Tirupati (13.63°N, 79.4°E), India, in August 2013 for continuous observations of horizontal winds in the mesosphere and lower thermosphere (MLT). This manuscript describes the purpose of the meteor radar, system configuration, measurement techniques, its data products, and operating parameters, as well as a comparison of measured mean winds in the MLT with contemporary radars over the Indian region. It is installed close to the Gadanki (13.5°N, 79.2°E) mesosphere‐stratosphere‐troposphere (MST) radar to fill the region between 85 and 100 km where this radar does not measure winds. The present radar provides additional information due to its high meteor detection rate, which results in accurate wind information from 70 to 110 km. As a first step, we made a comparison of SVU MR‐derived horizontal winds in the MLT region with those measured by similar and different (MST and MF radars) techniques over the Indian region, as well as model (horizontal wind model 2007) data sets. The comparison showed an exquisite agreement between the overlapping altitudes (82–98 km) of different radars. Zonal winds compared very well, as did the meridional winds. The observed discrepancies and limitations in the wind measurement are discussed in the light of different measuring techniques and the effects of small‐scale processes like gravity waves. This new radar is expected to play an important role in our understanding of the vertical and lateral coupling of different regions of the atmosphere that will be possible when measurements from nearby locations are combined. Key Points: System description of newly installed meteor radar is provided First results along with validation using similar radars are provided Advantages and limitations of this new system are discussed